2012
DOI: 10.1097/ccm.0b013e318232d6b0
|View full text |Cite
|
Sign up to set email alerts
|

The Eldicus prospective, observational study of triage decision making in European intensive care units. Part II

Abstract: Despite the fact that elderly patients have more intensive care unit rejections than younger patients and have a higher mortality when admitted, the mortality benefit appears greater for the elderly. Physicians should consider changing their intensive care unit triage practices for the elderly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
134
2
7

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 187 publications
(156 citation statements)
references
References 15 publications
13
134
2
7
Order By: Relevance
“…These may include VOPs, those with chronic diseases or active malignant diseases. In the large Eldicus study the elderly patients (greater than 75 years old) were found to have more ICU rejections than younger ones (less than 75 years old) despite having a greater mortality benefit [3]. On the other hand, in a prospective French study, no survival benefit was found in VOPs who were admitted versus rejected patients [4].…”
Section: Triagementioning
confidence: 96%
See 1 more Smart Citation
“…These may include VOPs, those with chronic diseases or active malignant diseases. In the large Eldicus study the elderly patients (greater than 75 years old) were found to have more ICU rejections than younger ones (less than 75 years old) despite having a greater mortality benefit [3]. On the other hand, in a prospective French study, no survival benefit was found in VOPs who were admitted versus rejected patients [4].…”
Section: Triagementioning
confidence: 96%
“…As already discussed, there is a short-term mortality benefit of ICU admission of VOPs [3,32]. However, 1-year mortality appears equally poor in both admitted and refused very elderly patients [33].…”
Section: Long-term Sequelaementioning
confidence: 99%
“…In addition, we observed that too old patients with irreversible medical conditions were receiving advanced life care treatment notwithstanding higher ICU mortality [25]. Several studies pointed out that ICU refusal rates increase according to patient age, underlying disease, prior cognitive impairment, dependency status, and medical criteria [25][26][27][28].…”
Section: Discussionmentioning
confidence: 96%
“…Several studies pointed out that ICU refusal rates increase according to patient age, underlying disease, prior cognitive impairment, dependency status, and medical criteria [25][26][27][28]. Our ICU has an open model and the decision to admitted patients comes mainly from the external assistant physician and family, limiting our power to explore the recommendation.…”
Section: Discussionmentioning
confidence: 99%
“…Prospective, observational study of triage decisions, performed in 11 ICUs in 7 European countries showed that elderly patients have more ICU rejections and higher mortality than younger ones. On the other hand, differences between mortality of accepted versus rejected patients were greatest for older patients indicating that the benefit of ICU admission appears to be greater for the elderly [16,17]. Despite the fact that age is an important and independent predictor of mortality, it cannot be used as the main admission criterion, as the severity of an acute medical condition is much more strongly associated with mortality [18].…”
mentioning
confidence: 99%